Utilizing Expertise after Retirement - Ibrahim, Muhammad (Journal of Legal Sciences, 2025)
This research examines the legal framework governing the investment of retirees in Iraq, focusing on their employment after retirement, as one of the ways to benefit from the nation's human capital. The research reviewed the applicable legal provisions, both those related to rights and duties, particularly Resolution No. (361) of 1985 and Instructions No. (7) of 1985. It revealed their inconsistency with constitutional texts and modern laws, such as Labor Law No. (37) of 2015 and Retirement and Social Security Law No. (18) of 2023. The research argues that the absence of specific legislation regulating the employment of retirees has led to the disruption of their energies and their exclusion from the labor market, despite their expertise and competencies. Accordingly, the research calls for the issuance of a special national law addressing this issue, which would ultimately achieve a balance between retirement rights and freedom of work, thus contributing to economic and social development.